Heteroptera (Pentatomomorpha I) biodiversity of state national natural park «kulsay kulderi» (Experimental biology, 2020)
As a result of a study in the territory of the SNNP “Kulsay Kulderi” State Scientific-Production Enterprise in 19, 19 species from 4 families of Heteroptera were identified. Among them, a large number of species stands family Aradidae (9 species), Berytidae (6 species), in the remaining 2 families, only 1-3 species are known: Piesmatidae (3 species), Pyrrhocoridae (1 species). Phytophages - 10 species, mycetophages - 8 species, zoophytophage - 1 species prevail in trophic relationships. By confinement to the habitats, the Heteroptera State national natural park “Kulsay kulderi” is divided into several groups: dendrobionts (9 species), hortobionts (8 species), herpetobionts (1 species), herpeto-hortobionts (1 species). By the number of generations per year, the species of semi-winged SNNP “Kulsay kulderі” can be divided into the following groups: acyclic (9 species), monovoltine (6 species), bivoltine (2 species), multivoltine (2 species). Heteroptera are characterized by wintering at different stages of development. In most species, a winter break occurs at the adult stage - 11 species, but few species winter at the adult stage and larvae of all stages - 7 species and 1 species at the larval stage. The Heteroptera SNNP “Kulsay kulderі” is a member of the mesophilic environmental group.Key words: Heteroptera, State National Natural Park “Kulsay kulderi”, South-East Kazakhstan.